Flow cytometry immunophenotyping in integrated diagnostics of patients with newly diagnosed cytopenia: one tube 10‐color 14‐antibody screening panel and 3‐tube extensive panel for detection of MDS‐related features. (14th May 2015) - Porwit, A.; Rajab, A.
Summary: Acute leukemia, myelodysplastic syndromes (MDS), myeloproliferative neoplasms and lymphomas are the most prevalent diagnoses in adults presenting with new onset cytopenia. Here, we describe two 10‐color panels of surface markers (screening and comprehensive panel) applied at the Flow Cytometry Laboratory, University Health Network, Toronto, ON, Canada. A 10‐color flow cytometry is applied using the stain–lyse–wash sample preparation method. In patients with <10% blasts and no clear involvement by hematological malignancy based on cytomorphological evaluation of bone marrow (BM) smear, the recently published one‐tube 10‐color 14‐antibody screening panel is applied. This panel allows detection of major B‐ and T‐cell abnormalities, enumeration of cells in blast region (CD45 dim), and gives insight into myeloid BM compartment, including calculation of four‐parameter score for MDS‐related abnormalities. In patients who present with ≥10 – <20% blasts in blood or BM smears, a comprehensive three‐tube panel of surface markers is used up front. The analysis is focused on the detection of abnormal antigen expression patterns not seen in normal/reactive BM, according to the guidelines developed by International/European LeukemiaNet Working Group for Flow Cytometry in MDS. In patients with ≥20% blasts, an additional tube is added to allow the detection of cytoplasmic markers necessary to diagnose mixed phenotype acute leukemia.